Method for inhibiting leakage current of alscn ferroelectric capacitor memory based on weak base solution treatment
Patent Information
- Application Number
- CN202611071820.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-20
AI Technical Summary
[0005]然而,上述方法存在明显不足,高温退火工艺不仅破坏与先进CMOS后端工艺的兼容性,还会增加整体工艺复杂度,同时还可能引发界面扩散或应力松弛等问题
1、本发明通过弱碱溶液浸泡的方式对AlScN薄膜进行处理,特异性促进AlScN薄膜中氮原子与铝、钪金属原子的成键反应,直接填补材料生长过程中产生的氮空位缺陷,降低或消除了禁带中作为载流子输运通道的缺陷能级,相比传统的AlScN铁电电容,本发明的漏电流可大大降低,解决了传统AlScN铁电电容高漏电流导致的器件功耗过高问题。
Smart Images

Figure CN122641023B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ferroelectric capacitor storage device technology, and in particular to a method for suppressing leakage current of AlScN ferroelectric capacitor storage device based on weak alkaline solution treatment. Background Technology
[0002] Compared to traditional ferroelectric capacitor memory devices, ferroelectric capacitor memory based on the emerging aluminum scandium nitride (AlScN) material has attracted much attention due to a series of significant advantages. Specifically, AlScN material has a higher remanent polarization intensity, far exceeding that of traditional ferroelectric materials (such as PZT or HZO). This characteristic can provide memory devices with a larger read / write window and stronger noise immunity. Simultaneously, AlScN also exhibits excellent thermal stability, meeting the application requirements in high-temperature environments. In terms of process compatibility, AlScN has a lower thermal budget (typically with process temperatures below 200°C), making it highly compatible with CMOS back-end processes. These advantages make AlScN-based ferroelectric capacitor memory a promising candidate for applications in fields with stringent requirements for high temperature, high radiation, and high reliability, such as medical electronics, edge computing, and aerospace.
[0003] However, AlScN-based ferroelectric capacitor memories currently face a key technical bottleneck: high leakage current. This issue significantly impacts device performance. First, the large leakage current accumulates substantial Joule heat within the device during long-term electrical cycling tests, leading to localized temperature increases, which accelerates dielectric breakdown and significantly reduces device durability. Existing research shows that the durability of AlScN-based ferroelectric capacitor memories is generally only 10... 5 ~10 7 The number of read / write cycles is far from meeting the 10 required by commercial non-volatile memory. 10 The leakage current is above average. Secondly, the high leakage current severely limits the reduction of AlScN film thickness. In thinner AlScN films, the electric field strength generated by applying the same voltage is significantly enhanced, leading to a sharp increase in leakage current. This makes it difficult for AlScN to meet the requirements of low-voltage, high-speed, and high-density integration applications. Furthermore, high leakage current also reduces the device's breakdown voltage, making it prone to hard breakdown failure under high-voltage operating conditions, further restricting its operating voltage and reliability in practical circuit applications.
[0004] Experiments have confirmed that the leakage current of AlScN-based ferroelectric capacitor memory devices mainly originates from nitrogen vacancy defects that are unavoidably generated during material growth. These nitrogen vacancies introduce defect energy levels in the bandgap, becoming transport channels for charge carriers, thus significantly increasing the leakage current. To address the problem of rapidly increasing leakage current, corresponding solutions have been proposed: high-temperature rapid thermal annealing (typically at temperatures above 400℃) can repair nitrogen vacancies to some extent and reduce leakage current; thin film deposition in a nitrogen-rich gas atmosphere can also reduce the formation of nitrogen vacancies at the source.
[0005] However, the above methods have significant drawbacks. High-temperature annealing not only compromises compatibility with advanced CMOS back-end processes but also increases overall process complexity and may cause problems such as interface diffusion or stress relaxation. While nitrogen atmosphere growth can improve film quality to some extent, it has high equipment requirements, a narrow control window, and cannot completely eliminate existing nitrogen vacancy defects.
[0006] Therefore, there is an urgent need to develop a simple and low-temperature compatible processing method that can effectively repair or reduce nitrogen vacancies in AlScN films, thereby significantly reducing leakage current and improving device durability and breakdown characteristics. Summary of the Invention
[0007] The purpose of this invention is to address the shortcomings of the prior art by providing a method for suppressing leakage current in AlScN ferroelectric capacitor memory based on weak alkaline solution treatment.
[0008] The objective of this invention is achieved through the following technical solution: a method for suppressing leakage current in AlScN ferroelectric capacitor memory based on weak alkaline solution treatment, comprising the following steps:
[0009] Step 1: Grow a first metal thin film layer on the substrate to form the bottom electrode; Step 2: Growing AlScN films on metal films; Step 3: Immerse the device prepared in Step 2 in a weak alkaline solution for surface treatment. The weak alkaline solution promotes the bonding between nitrogen atoms and metal atoms in the AlScN film and reduces the nitrogen vacancy concentration in the AlScN film. Step 4: Grow a second metal thin film layer on the AlScN thin film to form the top electrode; Step 5: Form a photoresist hard mask pattern layer on the top electrode using photolithography; Step 6: Etch the top electrode based on the photoresist hard mask pattern.
[0010] Preferably, in step three, the weak alkaline solution is a 2.38% tetramethylammonium hydroxide solution, ammonia, or N-methylpyrrolidone solution, the soaking temperature is 50-150℃, and the soaking time is 1-5 minutes.
[0011] Preferably, in step three, ultrasonic vibration is applied to the weak alkaline solution with an ultrasonic power of 50~200 W, a frequency of 40k~100 kHz, and a temperature of 30~50 ℃.
[0012] Preferably, the first metal thin film layer in step one and the second metal thin film layer in step four are both single metal layers or composite metal layers composed of at least two metal materials. The metal materials of the single metal layer or composite metal layer are selected from platinum, titanium, and molybdenum. The growth process of the first metal thin film layer and the second metal thin film layer is selected from one of magnetron sputtering, molecular beam epitaxy, and electron beam evaporation. The thickness range of the first metal thin film layer and the second metal thin film layer is 10~100nm.
[0013] Preferably, the first metal thin film layer in step one is a titanium-platinum composite metal layer, which is prepared by magnetron sputtering with a deposition vacuum of 1~5×10⁻⁶. -5 The growth temperature is 200~400℃, the sputtering rate is 0.1~3Å / s, the sputtering power is 50~200W, and the deposition time is 5~20min; the thickness of the platinum metal layer is 10~50nm.
[0014] Preferably, the second metal thin film layer in step four is a titanium-platinum composite metal layer, and the growth process is electron beam evaporation with a deposition vacuum degree ranging from 1 to 5 × 10⁻⁶. -5 The growth temperature range is 200~400℃, the evaporation rate range is 0.1~3Å / s, the electron beam current range is 20-200mA, the deposition time is 5~20min, and the deposition thickness is 10~50nm.
[0015] Preferably, the AlScN thin film in step two is prepared using any one of magnetron sputtering, electron beam evaporation, or metal-organic chemical vapor deposition. The scandium doping content in the AlScN thin film ranges from 10% to 35%, and the thickness of the AlScN thin film ranges from 10 to 150 nm.
[0016] Preferably, the AlScN thin film is prepared by magnetron sputtering, with a scandium doping content of 30% and a thickness of 100 nm.
[0017] Preferably, the etching process in step six uses one or more of plasma etching, reactive ion etching, or ion beam etching.
[0018] Preferably, plasma etching is used for etching, with an argon flow rate of 1~100 sccm, a trifluoromethane flow rate of 1~100 sccm, and an etching time of 5~10 min.
[0019] The beneficial effects of this invention are: 1. This invention treats AlScN thin films by immersing them in a weak alkaline solution, which specifically promotes the bonding reaction between nitrogen atoms and aluminum and scandium metal atoms in the AlScN thin film. This directly fills the nitrogen vacancy defects generated during material growth, reduces or eliminates the defect energy levels in the band gap that serve as carrier transport channels. Compared with traditional AlScN ferroelectric capacitors, the leakage current of this invention can be greatly reduced, solving the problem of excessive power consumption caused by the high leakage current of traditional AlScN ferroelectric capacitors.
[0020] 2. Compared to existing leakage current suppression methods such as high-temperature annealing, this invention has significant advantages in process compatibility and mass production: The processing temperature of this invention is only 50~150℃, far below the 200℃ thermal budget limit of CMOS back-end processes, avoiding problems such as interface diffusion, stress relaxation, and metal electrode oxidation. It can be directly integrated into existing CMOS manufacturing processes and has high compatibility with existing CMOS manufacturing technologies. The processing technology of this invention is simple, adding only a weak alkaline solution immersion step after AlScN thin film deposition. It does not require modification of existing semiconductor production lines, and the raw materials for weak alkaline solutions are inexpensive and readily available, reducing processing costs. In contrast, traditional high-temperature annealing processes require specialized annealing furnaces and other equipment, resulting in high equipment costs, long annealing times, complex processes, and greater processing difficulty. Attached Figure Description
[0021] Figure 1 This is a flowchart of the method steps of the present invention.
[0022] Figure 2 Comparison of X-ray photoelectron spectroscopy (XPS) spectra of AlScN films before and after treatment with a weak alkaline solution.
[0023] Figure 3 This is a comparison of the leakage current of AlScN ferroelectric capacitors treated with a weak alkaline solution and those not treated with a weak alkaline solution. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0025] Those skilled in the art should understand that, in the disclosure of this invention, the terms "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the above terms should not be construed as limiting this invention.
[0026] It is understood that the term "a" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element can be one, while in another embodiment, the number of the element can be multiple, and the term "a" should not be understood as a limitation on the number.
[0027] like Figures 1 to 3 As shown, a method for suppressing leakage current in AlScN ferroelectric capacitor memory based on weak alkaline solution treatment includes the following steps: Step 1: Grow a first metal thin film layer on the substrate to form the bottom electrode.
[0028] In this step, a silicon wafer is selected as the substrate. Before growing the first metal thin film layer on the substrate, the substrate is cleaned and dried in advance. The cleaning and drying methods are as follows: First, the substrate is ultrasonically cleaned for 1-20 minutes with acetone, isopropanol and deionized water respectively. After cleaning, it is dried with a nitrogen gun.
[0029] Acetone effectively removes grease, fingerprints, photoresist residue, organic protective films, and other organic impurities picked up during production and transportation from the silicon wafer surface. This prevents the presence of organic contaminants on the substrate from forming an insulating interlayer between the bottom electrode metal and the silicon substrate, thus increasing contact resistance. It also prevents the presence of organic contaminants from affecting the growth of subsequent thin film layers. Isopropanol completely replaces residual acetone on the substrate surface (acetone and isopropanol are miscible), preventing ring-shaped marks or spots from being left on the surface after direct drying of acetone. It further removes weakly polar organic contaminants that acetone cannot dissolve and reduces surface tension, making it easier for deionized water to uniformly wet the substrate surface.
[0030] In some embodiments of this application, the substrate is first cleaned with acetone for 5 minutes, then with isopropanol for 5 minutes. Acetone is soluble in isopropanol solution, which helps isopropanol remove excess acetone and avoids affecting the performance of the substrate and device. Finally, the substrate is cleaned with deionized water for 5 minutes to complete the cleaning. After the substrate is cleaned, it is thoroughly dried with a nitrogen gun.
[0031] In this step, the first metal thin film layer is a single metal layer or a composite metal layer composed of at least two metal materials. The metal materials of the single metal layer or the composite metal layer are selected from platinum, titanium, and molybdenum. The growth process of the first metal thin film layer is selected from one of magnetron sputtering, molecular beam epitaxy, and electron beam evaporation. The thickness of the first metal thin film layer is in the range of 10~100nm.
[0032] In some embodiments of this application, the first metal thin film layer is a titanium-platinum composite metal layer, which is prepared by magnetron sputtering with a deposition vacuum degree of 1~5×10⁻⁶. -5 The sccm deposition process involved a growth temperature of 200-400℃, a sputtering rate of 0.1-3 Å / s, a sputtering power of 50-200 W, and a deposition time of 5-20 min. The platinum metal layer thickness ranged from 10 to 50 nm. Setting the platinum metal layer thickness to 10-50 nm balances both film quality and device miniaturization. An excessively thin metal layer would result in poor quality, while an excessively thick metal layer would hinder memory miniaturization.
[0033] Step 2: Grow AlScN thin films on metal films.
[0034] In this step, the AlScN thin film is prepared using any one of magnetron sputtering, electron beam evaporation, or metal-organic chemical vapor deposition. The scandium doping content in the AlScN thin film ranges from 10-35%, and the thickness of the AlScN thin film ranges from 10-150 nm.
[0035] The AlScN film deposition thickness is set in the range of 10~150nm, balancing crystal quality and turn-on voltage. If the AlScN film is too thin, the crystal quality will be poor, resulting in high leakage current and directly affecting the overall performance of the device; if the AlScN film is too thick, the turn-on voltage will be too high.
[0036] In some embodiments of this application, the AlScN thin film is prepared by magnetron sputtering, the scandium doping content is 30%, and the deposition thickness of the AlScN thin film is 100 nm.
[0037] Step 3: Immerse the device prepared in Step 2 in a weak alkaline solution for surface treatment. The weak alkaline solution promotes the bonding between nitrogen atoms and metal atoms in the AlScN film and reduces the nitrogen vacancy concentration in the AlScN film.
[0038] In AlScN ferroelectric capacitors, the leakage current mainly originates from nitrogen vacancy defects that are unavoidable during growth. These defects introduce deep energy levels into the band gap, becoming transport channels for charge carriers. In this application, a weak alkaline solution directly repairs or reduces nitrogen vacancies through chemical action, thereby blocking the tunneling and hopping transport paths of charge carriers and fundamentally reducing the leakage current.
[0039] The principle of reducing nitrogen vacancy concentration through weak alkaline solutions is as follows: Hydroxide ions (OH-) in weak alkaline solutions... - The negatively charged hydroxyl ions are strongly attracted by the positively charged dangling metal sites surrounding nitrogen vacancies, preferentially adsorbing on defect-rich surfaces and near-surface regions (0-20 nm), rather than on the neutral crystal lattice surface, resulting in selective adsorption of hydroxyl ions. The adsorbed hydroxyl ions form temporary coordination bonds between metal atoms. This process pulls some of the electron clouds of the metal atoms toward the oxygen atoms, significantly weakening the original covalent bonds between the metal atoms and adjacent nitrogen atoms, thus lowering the breaking energy barriers of Al-N (aluminum-nitrogen) and Sc-N (scandium-nitrogen) bonds. At specific heating temperatures, short-range diffusion of nitrogen, aluminum, and scandium atoms is promoted in the surface and near-surface regions, allowing free nitrogen atoms to combine with metal vacancies in the lattice, and simultaneously allowing free metal atoms to combine with nitrogen vacancies, achieving lattice self-repair and effectively filling nitrogen vacancy defects. The significant reduction in nitrogen vacancies effectively solves the problem of high leakage current, ultimately leading to the fabrication of AlScN-based ferroelectric capacitor memories with fewer nitrogen vacancy defects, lower leakage current, and excellent durability and breakdown characteristics.
[0040] During the weak alkali solution treatment process, the concentration (alkalinity) of the weak alkali solution is strictly controlled to ensure that the weak alkali solution has a relatively mild alkalinity, so that the entire immersion treatment process will not damage the ferroelectric crystal structure inside the AlScN film.
[0041] The weak alkaline solution used is a 2.38% tetramethylammonium hydroxide solution (TMAH), a 1%~5% ammonia solution or an N-methylpyrrolidone solution. The soaking temperature is 50~150℃ and the soaking time is 1~5 minutes.
[0042] In some embodiments of this application, the weak alkaline solution is a 2.38% TMAH solution, the soaking temperature is 50~100℃, and the soaking time is 1~3min.
[0043] Furthermore, during the immersion treatment of the device, ultrasonic vibration is applied to the weak alkaline solution. The ultrasonic power is 50-200 W, the frequency is 40 kHz-100 kHz, and the temperature is 30-50 °C. By applying ultrasonic vibration and utilizing the ultrasonic cavitation effect, a transient high-pressure shock wave is generated on the device surface. This strong physical action can effectively break the diffusion boundary layer at the solid-liquid interface on the thin film surface and accelerate the diffusion of OH-.- Ions penetrate the shallow surface layer of the film and even internal defects, thereby significantly improving the neutralization and repair efficiency of nitrogen vacancies. In addition, ultrasound can simultaneously remove particulate contaminants that may be adsorbed on the film surface, preventing them from blocking defect sites and ensuring the uniformity of the treatment effect.
[0044] like Figure 2 As shown, Figure 2 The image shows a comparison of the X-ray photoelectron spectroscopy (XPS) spectra of AlScN ferroelectric films before and after weak alkali treatment. It is clear from the image that immersion in weak alkali solution directly promotes the formation of N-Al / N-Sc bonds and significantly reduces the nitrogen vacancy concentration.
[0045] like Figure 3 As shown, from Figure 3 It can be clearly seen that, compared with traditional AlScN ferroelectric capacitors, the leakage current of the present invention can be greatly reduced after being soaked in a weak alkaline solution, thus solving the problem of excessive power consumption caused by the high leakage current of traditional AlScN ferroelectric capacitors.
[0046] Step 4: Grow a second metal thin film layer on the AlScN thin film to form the top electrode.
[0047] In this step, the second metal thin film layer is a single metal layer or a composite metal layer composed of at least two metal materials. The metal materials of the single metal layer or the composite metal layer are selected from platinum, titanium, and molybdenum. The growth process of the second metal thin film layer is selected from one of magnetron sputtering, molecular beam epitaxy, and electron beam evaporation. The thickness of the second metal thin film layer is in the range of 10~100nm.
[0048] In some embodiments of this application, the second metal thin film layer is a titanium-platinum composite metal layer, the growth process is electron beam evaporation, and the deposition vacuum degree ranges from 1 to 5 × 10⁻⁶. -5 The growth temperature range is 200~400℃, the evaporation rate range is 0.1~3Å / s, the electron beam current range is 20~200mA, the deposition time is 5~20min, and the deposition thickness is 10~50nm.
[0049] Step 5: Use photolithography to form a photoresist hard mask pattern layer on the top electrode.
[0050] The specific method for this step is as follows: S1: A uniform photoresist film is formed on the surface of the top electrode using a spin coating process; S2: Perform a first drying of the photoresist film. The purpose of this step is to remove most of the organic solvents from the photoresist, improve its adhesion, uniformity, and mechanical strength, and at the same time avoid the formation of bubbles during exposure. S3: Precisely align the memory cell array pattern on the mask with the wafer, and then use ultraviolet light to cause a photochemical reaction in the photoresist (photolithography): S4: Utilizing the property that the exposed areas of the positive photoresist are soluble in the developer, the exposed photoresist is removed using the developer to form the desired pattern. S5: Secondary drying. The purpose of secondary drying is to further remove residual solvents in the photoresist, enhance the adhesion between the photoresist and the top electrode, and improve the photoresist's resistance to plasma etching, ultimately forming a photoresist hard mask pattern layer.
[0051] The photoresist type can be 5350, AZ1518, etc., and the thickness of the photoresist hard mask pattern layer is 1~3μm.
[0052] Step 6: Etch the top electrode based on the photoresist hard mask pattern.
[0053] The etching process in this step can be one or more of plasma etching, reactive ion etching, or ion beam etching.
[0054] In some embodiments of this application, plasma etching is used for etching, with an argon flow rate ranging from 1 to 100 sccm, a trifluoromethane (CHF3) flow rate ranging from 1 to 100 sccm, and an etching time of 5 to 10 min.
[0055] After etching, the top electrode is divided into several top electrode units. Each top electrode unit, together with its corresponding AlScN thin film and bottom electrode, constitutes an MFM capacitor unit.
[0056] This invention treats AlScN thin films by immersing them in a weak alkaline solution, which specifically promotes the bonding reaction between nitrogen atoms and aluminum and scandium metal atoms in the AlScN thin film. This directly fills the nitrogen vacancy defects generated during material growth, reducing or eliminating the defect energy levels in the band gap that serve as carrier transport channels. Compared with traditional AlScN ferroelectric capacitors, the leakage current of this invention can be greatly reduced, solving the problem of excessive power consumption caused by the high leakage current of traditional AlScN ferroelectric capacitors.
[0057] Compared to existing leakage current suppression methods such as high-temperature annealing, this invention has significant advantages in process compatibility and mass production: the processing temperature of this invention is only 50~150℃, far below the 200℃ thermal budget limit of CMOS back-end processes, avoiding problems such as interface diffusion, stress relaxation, and metal electrode oxidation. It can be directly integrated into existing CMOS manufacturing processes and has high compatibility with existing CMOS manufacturing technologies. The processing technology of this invention is simple, adding only a weak alkaline solution immersion step after AlScN thin film deposition. It does not require modification of existing semiconductor production lines, and the raw materials for weak alkaline solutions are inexpensive and readily available, reducing processing costs. In contrast, traditional high-temperature annealing processes require specialized annealing furnaces and other equipment, resulting in high equipment costs, long annealing times, complex processes, and greater processing difficulty.
[0058] This invention is not limited to the preferred embodiments described above. Anyone can derive other products in various forms under the guidance of this invention. However, regardless of any changes in shape or structure, any technical solution that is the same as or similar to this application falls within the protection scope of this invention.
Claims
1. A method for suppressing leakage current in AlScN ferroelectric capacitor memory based on weak alkaline solution treatment, characterized in that, Includes the following steps: Step 1: Grow a first metal thin film layer on the substrate to form the bottom electrode; Step 2: Growing AlScN films on metal films; Step 3: Immerse the device prepared in Step 2 in a weak alkaline solution for surface treatment. The weak alkaline solution promotes the bonding between nitrogen atoms and metal atoms in the AlScN film and reduces the nitrogen vacancy concentration in the AlScN film. Step 4: Grow a second metal thin film layer on the AlScN thin film to form the top electrode; Step 5: Form a photoresist hard mask pattern layer on the top electrode using photolithography; Step 6: Etch the top electrode based on the photoresist hard mask pattern.
2. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 1, characterized in that, In step three, the weak alkaline solution used is a 2.38% tetramethylammonium hydroxide solution, ammonia, or N-methylpyrrolidone solution. The soaking temperature is 50~150℃, and the soaking time is 1~5 minutes.
3. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 2, characterized in that, In step three, ultrasonic vibration is applied to the weak alkaline solution with an ultrasonic power of 50~200 W, a frequency of 40 k~100 kHz, and a temperature of 30~50 ℃.
4. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 1, characterized in that, The first metal thin film layer in step one and the second metal thin film layer in step four are both single metal layers or composite metal layers composed of at least two metal materials. The metal materials of the single metal layer or composite metal layer are selected from platinum, titanium, and molybdenum. The growth process of the first metal thin film layer and the second metal thin film layer is selected from one of magnetron sputtering, molecular beam epitaxy, and electron beam evaporation. The thickness range of the first metal thin film layer and the second metal thin film layer is 10~100nm.
5. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 4, characterized in that, The first metal thin film layer in step one is a titanium-platinum composite metal layer, which is prepared by magnetron sputtering with a deposition vacuum of 1~5×10⁻⁶. -5 The growth temperature is 200~400℃, the sputtering rate is 0.1~3Å / s, the sputtering power is 50~200W, and the deposition time is 5~20min; the thickness of the platinum metal layer is 10~50nm.
6. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 4, characterized in that, The second metal thin film layer in step four is a titanium-platinum composite metal layer, grown using electron beam evaporation with a deposition vacuum level ranging from 1 to 5 × 10⁻⁶. -5 The growth temperature range is 200~400℃, the evaporation rate range is 0.1~3Å / s, the electron beam current range is 20-200mA, the deposition time is 5~20min, and the deposition thickness is 10~50nm.
7. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 1, characterized in that, In step two, the AlScN thin film is prepared using any one of magnetron sputtering, electron beam evaporation, or metal-organic chemical vapor deposition. The scandium doping content in the AlScN thin film ranges from 10% to 35%, and the thickness of the AlScN thin film ranges from 10% to 150 nm.
8. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 7, characterized in that, The AlScN thin film was prepared by magnetron sputtering with a scandium doping content of 30% and a thickness of 100 nm.
9. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 7, characterized in that, The etching process in step six employs one or more of plasma etching, reactive ion etching, or ion beam etching.
10. The method for suppressing leakage current of AlScN ferroelectric capacitor memory based on weak alkaline solution treatment according to claim 9, in step six, plasma etching is used for etching, the argon flow rate is in the range of 1~100 sccm, the trifluoromethane flow rate is in the range of 1~100 sccm, and the etching time is 5~10 min.
Citation Information
Patent Citations
AlScN device with low working voltage and low leakage current and preparation method thereof
CN119342839A
Van der Waals buffer layer-based scandium aluminum nitride film low-temperature growth method and heterostructure
CN122138623A